(untitled) (Foro de Educacion, 2022)
Research has shown that in many contexts, the transformation of the public sector associated with new public management (NPM) reforms and performance-based accountability (PBA) has had profound implications for public sector workers’ practices, identities and emotional experiences. Focusing on the education sector, in this paper we aim to contribute to the understanding of the relationship between PBA policies and teachers’ emotions by conducting a scoping review of the scientific literature. Our review, which is based on a final sample of 63 articles published between the years 2000-2021 obtained from the SCOPUS database, identifies two main bodies of research. The first deals with an examination of teachers’ emotions and shows how PBA is a crucial part of a changing professional environment that accentuates and/or modifies feelings and emotions already inherent to the teaching profession. The focal point of the second strand of research is the effect of PBA on teachers’ emotions; here, we identify research exploring the emotional effects of PBA, as well as the mechanisms behind different emotional experiences, how teachers deal with emotions emerging from PBA policies and a number of factors that intensify or weaken the emotional impact of PBA. On the basis of our review, limitations of existing research and gaps in the understanding of the relationship between PBA and teachers’ emotions are identified and promising lines of future research formulated.